Dental and Temporomandibular Joint Pathology of the California Mountain Lion (Puma concolor couguar). Issue 2 (February 2017) - Aghashani, A.; Kim, A.S.; Kass, P.H.; Verstraete, F.J.M.
Summary: Skulls from 91 California mountain lions ( Puma concolor couguar ) were examined macroscopically and radiographically. The majority of the skulls were from young adult animals (57.1%). The skull specimens were from 42 male (46.1%) and 34 female (37.4%) animals, while the gender was unknown for the remainder. The majority (94.5%) of teeth were present for examination. Only 11 teeth were identified as absent congenitally; five of these teeth were maxillary first molar teeth and three were maxillary second premolar teeth. Abnormal tooth morphology was identified in 3.5% of teeth. The most common abnormality in tooth form was abnormally large crowns of the maxillary first molar teeth. Teeth with an abnormal number of roots were uncommon ( n  = 21). Ninety-one teeth were found to have an abnormal number of roots, most often two-rooted maxillary first molar teeth instead of the expected one root. The most prevalent dental lesions found in the California mountain lion were attrition/abrasion (93.4%), tooth fractures (80.2%) and periodontitis (38.5%). Less common dental lesions were tooth resorption ( n  = 32 teeth) and endodontal disease ( n  = 29 teeth).